PENGARUH PENGANGGURAN DAN PERTUMBUHANEKONOMI TERHADAPPEMBANGUNAN MANUSIADI PROVINSIKALIMANTAN BARAT - B01111088, Sulina (Jurnal Pembangunan dan Pemerataan, 2015)
This study entitled with The â€œEffect of Unemployment and Economic Growth to Human Development in Province West Kalimantan,â€ which is aimed to test and to analyze the influence of unemployment and Economic Growth in Province West Kalimantan. The research hypothesis is tested using analyze multiple linear regression model, using secondary data of times series and Cross Section from Central Bureau of Statistics Indonesian and Province West Kalimantan. Based on the results of studies using analyza multiple linear regression model, it showed that the of Unemployement and Economy Growth has a significant effect to the human development in Province West Kalimantan. The ofÂ  unemployment significantly influences Human Development, and negative, with the coeficient -0,323. Economy growth significantly influences human development, and positive, with the regression coeficient 0,200. Both of independent variables and control variable can explainÂ  the variations or changes of human development around 99,84%. KeywordsÂ  : Human develovment, Unemployment And Economic growth